TRADISI “LOUWE BASUDARAO” DALAM PERSIAPAN PERNIKAHAN MASYARAKAT NEGERI SIRI SORI ISLAM (Suatu Budaya dan Perspektif Hukum Islam) - Muhammad Ali Holle (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Describes the tradition of Louwe Basudarao culture in marriage by the Siri Sori Islam Society in the perspective of Islamic law. From the results of the study with theological, physiological, sociological and anthropological approaches, it can be understood that Louwe Basudarao is a Local Culture carried out by the Siri Sori Islam Society in preparation for marriage. This tradition has been rooted in the procession before the marriage of the community so that none of Louwe Basudarao's activities escaped even though it was carried out in various different regions. Louwe Basudarao tradition with the purpose and meaning contained in it generally corresponds to the principles of Islamic law, because 1) contains a logical benefit 2) generally applies to the community in a place or at least among the majority of its people, 3) has been valid for a long time, not new customs that emerge later, 4) do not conflict with the arguments of shara that exist or conflict with the general principles of Islamic Shari'a. Marriage is the obligation of mankind to fulfill biological needs and advice in Islam to follow the Sunnah of the Apostle in creating a good generation and believers, so before marriage first do a series of arrangements for Mahar deliberations, then the bride and groom each perform Louwe Basudara. The provision of money in Louwe has been set a standard fee on the basis of mutual consultation. This tradition has been carried out by the previous ancestors as a form of mutual standardism or helping each other in the event of the bride and groom's request to launch a marriage. at first, every family who wants to take care of their child will first conduct friendship (family gathering) between a large family of clan eyes and notify and coordinate with the Chairperson of the IKKAASSI. Every Descendant or Siri Family in Islam wherever they are This Louwe Basudarao tradition has been carried out by ancestors since time immemorial to help each other and strengthen the brotherhood with the slogan of Mae Ipika Mese Tula Ehu Mese-Mese which means 'Come together to help each other'.